A new species of and a new transfer from the millipede genus Polydrepanum Carl, 1932 (Polydesmida, Paradoxosomatidae, Polydrepanini) - Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2018)
A new species of Polydrepanum Carl, 1932, is described and illustrated in detail from the Eastern Ghats of India: P. fissum sp. nov. One new combination of species misplaced in Polydrepanum is established: Telodrepanum implicatum (Carl, 1941) comb. nov.. All the nominal Polydrepanum spp. are keyed and the known distribution of the genus is mapped.